DAMPAK PERUBAHAN ORGANISASIONAL INSTITUSI PENDIDIKAN TINGGI KESEHATAN DALAM PERSPEKTIF MANAJEMEN - Nang Randu Utama (Universitas Negeri Malang, 2017)
Abstract: This study aims to obtain a picture of the impact of organizational changes in theinstitution of higher health education in the management perspective that occurred in thescope of educational institutions belong to the Ministry of Health of the Republic of Indonesia.This study used a qualitative approach by conducting case study at Palangka Raya HealthPolytechnic. The results of the study are as follows: (1) organizational change resulted inchanges in the organizational structure; (2) organizational change also resulted in changes inthe construction of facilities and infrastructure; (3) work system is no longer leads to routine,more dynamic, and flexible; (4) efficiency in learning and budget planning is done througha single door and centralized including personnel affairs, finance and general administration(ADUM) and academic and student affairs administration (ADAK); (5) organizationalchange is also accompanied by changes in the behavior of members of the organization, (6)organizational change is also related to leadership factors; and (7) organizational change alsoaffect all forms of services that exist within the organization.Keyword: change, organizational change, health polytechnicAbstrak: Penelitian ini bertujuan untuk memperolah gambaran mengenai dampak perubahanorganisasional institusi pendidikan tinggi kesehatan dalam perspektif manajemen yang terjadidi lingkup institusi pendidikan Kementerian Kesehatan Republik Indonesia. Penelitian inimenggunakan pendekatan kualitatif dengan melakukan studi kasus pada institusi PoliteknikKesehatan Kemenkes Palangka Raya dalam perspektif manajemen. Hasil penelitian adalah:(1) perubahan organisasi mengakibatkan perubahan pada struktur organisasi; (2) perubahanorganisasi juga mengakibatkan perubahan pada pembangunan sarana dan prasarana; (3)perubahan pada sistem kerja yang tidak lagi mengarah pada rutinitas, namun lebih dinamis,dan fleksibel; (4) terjadi efisiensi dalam pembelajaran dan perencanaan anggaran yangdilakukan melalui satu pintu dan terpusat termasuk Urusan Kepegawaian, Keuangan danAdministrasi umum (ADUM) dan Administrasi Akademik dan Kemahasiswaan (ADAK);(5) perubahan organisasi juga disertai dengan perubahan perilaku anggota organisasi; DOI: https;//doi.org/10.17977/um025v1i32017p187